Household saving rates and the design of social security programmes : evidence from a country panel - Richard Disney (Center for Economic Studies and ifo Institute (CESifo), 2005)
I argue that the offsetting effect of social security contributions on household retirement saving depends on how closely the social security programme imitates a private retirement saving plan (i.e. the ?actuarial? component of the social security programme) – the closer the design of the programme to a private retirement saving plan, the higher the offset. I estimate the determinants of household saving rates in a cross-country panel, augmenting standard measures of social security programme generosity and cost by indicators that proxy the actuarial component of the programme. These indicators affect saving rates as predicted; moreover they also affect labour force participation rates of older women (but not men). The findings are consistent with the view that more actuarially-based public programmes are treated by participants as a mandatory saving programme rather than as a tax-and-transfer system, thereby raising labour force participation rates but also increasing the programme's substitutability for private retirement saving.
Keywords: E21; H24; G23; 330; social security reform; household saving; Soziale Sicherung; Sparen; Private Rentenversicherung; Gesetzliche Rentenversicherung; Crowding out; Schätzung; OECD-Staaten